A Praxis/future-driven Inclusive Science Learning Through STEAM-based Design Thinking Project - Thapaliya, Pratima (Innovative Research Journal, 2023)
Engaging the prospective science teacher in a praxis/future-driven orientation holding transformative STEAM-based design thinking project designing and implementing approach is new in the Nepalese science teacher education program. It could support critically reflecting on- action and in-action for reducing the gap between theory and practice for action. This paper attempted to explore the research question: How could I engage prospective science teachers in a STEAM-based design thinking project for a praxis/future-driven inclusive science learning? So, the transformative action research methodology has been launched in my workplace purposively by selecting eight research participants. I designed and implemented the STEAM-based design thinking project in my science classroom. It motivated my research participants to know this approach's conceptual, theoretical, and practical dimensions by actively participating in critical discourse. I viewed my and my participants' feelings, beliefs, and actions from the theoretical lens of critical-reflexive Bildung, which has the learners' high content and skills development orientation. It helped me to visualize the deep-rooted disempowering forces and the viable alternative ways for action. Moreover, it invited me to change my cultural reproduction-dominated science teaching. This research also envisages a curriculum as a mandala, pedagogy as/for the public good, and assessment as/for learning for praxis/future-driven science classrooms.